Presence of benzotriazoles, benzothiazoles and benzenesulfonamides in surface water samples by liquid chromatography coupled to high‐resolution mass spectrometry. Issue 3 (13th March 2019) - Hidalgo‐Serrano, Míriam; Borrull, Francesc; Marcé, Rosa M.; Pocurull, Eva
Abstract: An analytical method has been developed for the simultaneous determination of seven benzotriazole, five benzothiazole and four benzenesulfonamide derivatives in surface water samples. The procedure is based on solid‐phase extraction with Oasis HLB, followed by high‐performance liquid chromatography coupled to high‐resolution mass spectrometry. Apparent recoveries ranged from 40 to 101%, except for compounds the matrix effect of which was above ‐60%. The repeatability (n = 5) of the method was below 20% for all compounds except 4‐hydroxybenzotriazole in river water. The method limits of detection for most compounds ranged from 1 to 12 ng/L for both river water and seawater. The method was then used for the determination of the studied compounds in several river water and seawater samples from harbour and coastal areas. 1‐ H ‐Benzotriazole (up to 78 ng/L in river water and above the upper limit of the calibration curve in seawater) and 4‐methyl‐1‐ H ‐benzotriazole (up to 44 ng/L in river water and 338 ng/L in seawater) were the most abundant compounds quantified in the samples, even though 5‐methyl‐1‐ H ‐benzotriazole and 2‐hydroxybenzothiazole were also found in most samples. Some compounds were frequently found in certain types of samples, such as 2‐aminobenzothiazole in river water. Benzenesulfonamide derivatives could not be quantified in any sample.